Video Intervention in Statistics Learning as a Strategy to Increase Mathematics Learning Outcomes - Hendrowati, Tri Yuni; Faelasofi, Rahma (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
The COVID-19 pandemic requires the learning process to take place online, this has an impact on teachers who are required to creatively innovate unusual learning processes. This research aims to determine the difference in the average learning outcomes of students during online learning between the application of learning videos before and after receiving the learning video intervention treatment. The research instrument used was a test of statistics material. The learning outcomes test data obtained were processed by paired t-test. This research found that there was a difference in the average learning outcomes of students before and after the application of learning videos. The application of learning videos provides better learning outcomes than before using learning videos.